Analisis Tingkat Kepatuhan Hand Hygiene Perawat dalam Pencegahan Infeksi Nosokomial - Marfu'ah, Siti; Sofiana, Liena (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: Hospitals are required to provide good services matching with the given standards. People who received health services were faced with the risk of nosocomial infection. The incidence of infection was recorded in various countries nosocomial around 3.3%-9.2%. Hand hygiene was the most important thing to prevent the spread of infection. The purpose of this study was to determine nurse’s compliance with hand hygiene in effort of preventing efforts nosocomial in Ward Dahlia of RSUD Wonosari Yogyakarta. Method: This study was a qualitative descriptive study. The research subject was as many as 15 nurses with a total sampling, where as the interview with the head of the ward, nurses and other control and prevention of infection used purposive sampling. Collecting data was done by sheet checklist, interview and documents. Data were analyzed using Miles and Huberman. Results: The nurses in performing hand hygiene SOP have been appropriate but some not with the percentage of 80%. Nurse’s compliance in hand hygiene compliance based on five principles moment it was found that nurses in carrying out the moment 1 was by 66.7% and the moment 2 was 73.4%, the percentage was categorized as minimal compliance. Conclusion: Standard operating procedure of hand hygiene and infrastructure was well, the process of implementation of hand hygiene nurses have not all met the standards. Nurses mostly ignored the moment 1 and 2, the moment 3, 4 and 5 were in the category of good compliance. Monitoring and evaluation has been done.